Estudo de incorporação de whiskers de celulose em polietileno de baixa densidade (PEBD) - Teodoro, Kelcilene Bruna Ricardo (2014)
This research proposed the obtainment of cellulose whiskers from cotton fibers and their application in low density polyethylene matrix (LDPE). Cellulose whiskers was obtained from acid hydrolysis of cotton fibers and the reaction conditions were defined after study of different acid in hydrolysis reaction (under 45°C and 75 minutes, with HCl sample WCl, or H2SO4 sample WS, or mix of them in a proportion 1:1 sample WSCl). The main difference observed was the amount sulfate groups on whiskers surface due the use sulphuric acid in hydrolysis. These groups affected the properties of samples, increasing stability of whiskers in aqueous suspension, decreasing the tendency to agglomeration. However, due to these groups, cellulose is degraded at low temperatures. Once the nanocellulose (hydrophillic) needs to interact with LDPE (hydrophobic), two strategies was studied to compatibilize them: (i) production a nanocomposite based EVA poly (ethylene-covinyl acetate), a copolymer compatible with matrix and filler, since it have a polar phases (vinyl acetate monomer) and a nonpolar phase (ethylene monomer), and (ii) surface modification of cellulose whiskers by esterification reactions. Nanocomposites based EVA was prepared by polymeric solution where EVA was solubilized in mineral oil and then, the whiskers without surface modification (WS) was added, with aim dispersing them in LDPE. The characterizations this study showed that the solvent remained inside the structure polymeric, modifying their original properties and difficulting the interaction between cellulose and copolymer molecules. The sample WS and WCl was applied in esterification reactions with acetic acid, propionic acid and maleic anhydride. Whiskers extracted by hydrochloric acid and modified by maleic anhydride (WClMal), was produced by a simple methodology and presented thermal stability at processing temperatures. Thus, this sample was used to obtain nanocomposites with cellulose whiskers and LDPE, which was produced as films by extrusion process. Nanocomposites with LDPE and whiskers not modified (WCl) was produced to comparison. The characterizations of these materials confirmed the incorporation of whiskers in a polymeric matrix. The concentration that showed good dispersion and lower clusters was 1% (w/w) cellulose whiskers in LDPE matrix.